FEELINGS OF NATIONAL PRIDE IN ABDULHAMID CHOLPON - Karimov Abdusamad (Journals Park Publishing, 2022)
This article talks about Cholpon's ways to get rid of "bad luck" in literature, his enthusiasm in the process of social renewal. In addition, in this article you can see the analysis of several literary and critical heritages of Cholpon.
Keywords: National pride, spiritual existence, modern writers, literary and critical works, ideology.